Unusual Presentation of a Colonic Sarcoidosis - Daldoul, Sami (Hindawi Publishing Corporation, 2012)
Sarcoidosis is a multisystemic disorder of unknown cause that affects almost every tissue in the body. Colon is an extremely rare location of this disease. Clinical presentation, endoscopic appearances, and radiologic findings are not specific and may mimic much other affection. We report the case of a 64-year-old woman with inactive pulmonary sarcoidosis who presented alternating constipation and diarrhea. Colonoscopy revealed a stenotic tumor in the ascending colon. Histology failed to determine the nature of the lesion. Radiologic findings are those of a long stenotic tumor of the ascending colon associated with a multiple satellite lymphadenopathy. Endoscopic and radiologic descriptions are highly suggestive of a malignancy. The patient underwent a laparotomy, and a right hemicolectomy was performed. Examination of the resected specimen showed follicular structure with central epitheloid and giant cells and surrounding fibroblasts. These findings made the diagnosis of colonic sarcoidosis. The nonspecificity of the endoscopic and radiological signs of gastrointestinal sarcoidosis and the extreme rarity of colonic location make the preoperative diagnosis unlikely. The diagnosis will be then made only on histological examination of surgical specimens. We describe, through this observation, the results of paraclinical investigations that can suggest diagnosis and perhaps avoid surgery.